Liquid-infused nitric oxide-releasing (LINORel) silicone for decreased fouling, thrombosis, and infection of medical devices. Issue 1 (December 2017) - Goudie, Marcus; Pant, Jitendra; Handa, Hitesh
Abstract Recent reports on liquid-infused materials have shown promise in creating ultra-low fouling surfaces, but are limited in their ability to prevent bacterial proliferation and prevent platelet activation in blood-contacting applications. In this work, a liquid-infused nitric oxide-releasing (LINORel) material is created by incorporating the nitric oxide (NO) donorS -nitroso-acetylpenicillamine (SNAP) and silicone oil in commercial medical grade silicone rubber tubing through a solvent swelling process. This combination provides several key advantages over previous NO-releasing materials, including decreased leaching of NO donor, controlled release of NO, and maintenance of ultra-low fouling property of liquid-infused materials. The LINORel tubing reduces protein adhesion as observed using fluorescence imaging, and platelet adhesion (81.7 ± 2.5%)in vitro over a 2 h period. The LINORel combination greatly reduces bacterial adhesion and biofilm formation of two most common pathogens responsible for hospital acquired infections: gram-positiveStaphylococcus aureus and gram-negativePseudomonas aeruginosa (99.3 ± 1.9% and 88.5 ± 3.3% respectively) over a 7-day period in a CDC bioreactor environment. Overall, the LINORel approach provides a synergistic combination of active and passive non-fouling approaches to increase biocompatibility and reduce infection associated with medical devices.